The Feasibility of Developing Learning Videos on the Technique of Bioassay - Panjaitan*, Ruqiah Ganda Putri; Tenriawaru, Andi Besse; Silaen, Jayanti; Nikmah, Nur Alfiatun; Ire, Fetronila; Lestari, Liya Angga (Universitas Syiah Kuala, 2025)
The development of information and communication technology has a significant impact on the world of education, particularly in the provision of learning media. Video-based learning media has become an effective alternative for visualizing complex materials, such as in the bioassay technique course. This study aims to develop and assess the feasibility of educational videos as media for the Bioassay technique course, which includes material on testing using animal testing. This study uses the research and development (RD) method with a modified ADDIE development model consisting of four stages: analysis, design, development, and evaluation. Data collection techniques include validation by experts. The instrument used is a validation sheet with a Likert scale. The aspects assessed include format, content, and language. For the four indicators in the format aspect, a validity score of 1 was obtained. Similarly, for the three indicators in the content aspect, the validity score was also 1, and for the two indicators in the language aspect, the validity score remained at 1. Overall, from these three aspects, an average validation score of 1.00 was achieved, categorized as very high. Therefore, the video is deemed suitable to be used as a learning media in the bioassay technique course.